Eyesight to insight: evidence from urban eye health programme - Sahu, Ananta Basudev; Tripathi, Himadri; Buttan, Sandeep; P. N., Prasannakumar; Bhatia, Karuna (International Journal Of Community Medicine And Public Health, 2024)
India, with a population exceeding 1.486 billion, faces substantial challenges in urban eye health, particularly in densely populated states like Uttar Pradesh. This study delves into real-world impact of urban eye health programme, implemented in Kanpur and Prayagraj, Uttar Pradesh, aiming to identify success factors and examine the tangible effects of interventions through comprehensive endline study. Utilizing a hub-and-spoke model, the programme established base hospitals as hubs and vision centres as spokes, creating a network for affordable and accessible eye care. The project significantly improved accessibility, with over 85% in Kanpur and 97% in Prayagraj reporting easy access to vision centres. A shift in community behaviour was observed, with a preference for vision centres for eye examinations increasing from 5.6-64.6% in Kanpur and 10.6-57.1% in Prayagraj. The programme empowered women to prioritize their eye health, reaching 53% of women for eye screening. Community perception shifted positively, with over 82% in Prayagraj recognizing the programme’s pivotal role. In Kanpur, 87.5% of women actively take charge of their eye health decisions, while 99.1% do so in Prayagraj. This empowerment underscores programme commitment to providing equal access to eye care and demonstrates a strong focus on inclusivity and gender equality.